Praktik Manajemen Operasional dan Kinerja Pelabuhan Tanjung Emas Semarang: Studi Kasus Alokasi Tambatan, Penanganan Kontainer, dan Digitalisasi - Dewa, Adenanthera Lesmana; Mulatsih, Retno; Rahmasari, Lisda (Jurnal Ekonomi, Bisnis dan Manajemen, 2026)
Operational inefficiency remains a challenge for Indonesian branch ports, including Tanjung Emas Port in Semarang, where vessel turnaround, berth utilization, cargo handling, and inter-agency coordination affect service performance. This study aims to examine the association between berth scheduling, cargo and yard handling, and port information system digitalization with key port performance indicators, particularly vessel turnaround time, Berth Occupancy Ratio, yard occupancy ratio, and dwell time. A mixed documentary method was employed by synthesizing secondary evidence from port performance studies, DEA/SFA analyses, institutional documents, and national digitalization reports for the 2015–2025 period, with emphasis on the post-2020 operational environment. The findings show that Tanjung Emas records relatively favorable vessel turnaround performance in nominal terms, although relative efficiency results vary across DEA studies because of differences in comparator sets, model specifications, and data periods. Yard occupancy remains below the critical threshold but is projected to increase substantially by 2032. Dwell time is consistently associated with customs and quarantine documentation processes, while recent evidence identifies gate operations and stakeholder coordination as important operational constraints. Digitalization supports operational improvement, but its local evidence remains limited and still indicates risks related to system downtime, manual fallback, and interoperability gaps. The study implies that short-term improvement should prioritize parallel reform of documentary coordination and gate operations, while yard capacity and digital integration require proactive medium-term planning.